Spatiotemporal distribution patterns of cephalopods and their responses to changes in the marine environment in the coastal waters of Zhejiang, China - Liang, Jun; Zhou, Yongdong; Wu, Tian; Chen, Feng; Xu, Kaida; Fang, Guangjie; Zhang, Yazhou (Frontiers in Marine Science, 2025)
IntroductionLike pelagic fishes, cephalopods represent fishery resources with high worldwide potential and an important evolutionary node animal group. Thus, exploring the spatial and seasonal variations in cephalopod distribution and their associations with environmental factors is important for elucidating cephalopod diversity and the distribution of cephalopods under changing environmental conditions and for developing reasonable resource management and conservation measures.MethodsOn the basis of trawl survey data from 123 stations in the coastal waters of Zhejiang, China, in the spring and autumn of 2021, the relationships among the cephalopod species composition and diversity characteristics and the spatial and seasonal changes and environmental factors were investigated via the relative importance index (IRI), the alpha diversity index, and the GAM.ResultsThe results revealed that the cephalopods in the coastal waters of Zhejiang belonged to three orders, six families, and 10 genera and that the dominant species were gradually replaced by species of minor economic importance and endemic small-scale fishery species. In spring, Uroteuthis duvaucelii was the dominant species, the resource density in the southern coastal waters of Zhejiang was relatively high, and the overall distribution increased from northeast to southwest. In autumn, U. duvaucelii and Abralia multihamata were the dominant species, and the coastal waters of Zhejiang presented two high-density distribution areas in the northern and central waters, with lower resource density in the southern waters. Analysis of the alpha diversity index revealed relatively low cephalopod community diversity, with significant differences in spatial and seasonal distributions. The GAM revealed that, in spring, surface dissolved oxygen and sea bottom temperature led to significant changes in cephalopod resource density (p<0.05), and water depth significantly affected cephalopod resource density (p<0.01); in autumn, only water depth significantly affected cephalopod resource density (p<0.01).DiscussionThe cephalopod resources in the coastal waters of Zhejiang are under the dual stresses of fishing and environmental changes. The protection and restoration of traditional economic cephalopod resources are needed to ensure their sustainable development and utilization.